# Find Remainder of 4x^3-3x^2-8x+4 by x+1 using Remainder Theorem

The Remainder Theorem is an approach to Euclidean polynomial division. According to this theorem, dividing a polynomial P(x) by a factor (x - a), which is not an element of the polynomial, yields a smaller polynomial and a remainder. Here you can check the answer for Find Remainder of 4x^3-3x^2-8x+4 by x+1 using Remainder Theorem.

**Ex: ** x^2+2x+1,x+1 (or) x^2-1,x-1 (or) x^3-1,x+1

## How to Find Remainder of 4x^3-3x^2-8x+4 by x+1 using Remainder Theorem?

Let p(x) = 4x^3-3x^2-8x+4

The zero of x+1 is = -1.

So after P(x) is divided by x+1 we get the remainder i.e. P(-1).

Now, p(-1) = 4x^3-3x^2-8x+4 .

= (4)+(-8.x)+(-3.x^2)+(4.x^3)

By putting x = (-1) we can rewrite it as

= (4)+(-8.(-1))+(-3.(-1)^2)+(4.(-1)^3)

= (4)+(8)+(-3)+(-4)

= 19

âˆ´The remainder of given polynomial is 19.

### FAQs on Remainder Theorem of 4x^3-3x^2-8x+4 by x+1

**1. What is the remainder of 4x^3-3x^2-8x+4 by x+1?**

The Remainder of 4x^3-3x^2-8x+4 divided by x+1 is 19.

**2. How to Find Remainder of 4x^3-3x^2-8x+4 by x+1 using Remainder Theorem?**

Consider x+1 = 0 so that x = -1.

Substitute x = -1 in expression 4x^3-3x^2-8x+4 to get the remiander

Thus, 4x^3-3x^2-8x+4 divided by x+1 remainder is 19.

**3. Where can I obtain detailed solution steps for Remainder Theorem of 4x^3-3x^2-8x+4?**

The detailed steps for the Remainder Theorem of 4x^3-3x^2-8x+4 are compiled exclusively on our output page.